Squeezing the Interest Rate Smoothing Weight with a Hybrid Expectations Model - Efrem Castelnuovo (Fondazione Eni Enrico Mattei (FEEM), 2003)
Successful descriptions of short-term nominal interest rates inertial behavior have frequently been obtained with small scale macro models in which a Central Banker minimizes a loss function embedding an argument labelled as interest rate smoothing. The rationale for this argument is not straightforward. Indeed, there has been a lively debate about it in the literature. In this paper we perform an empirical exercise to evaluate the relationship existing between private sector's rational expectations and interest rate gradualism. Our findings strongly support rational expectations as an element capable to remarkably reduce the importance of the interest rate smoothing weight in replicating the observed path of the federal funds rate. However, we find a predominance of adaptive expectations in shaping the paths of inflation ad output gap. Our results also suggest that the Fed has followed a 'Strict Inflation Targeting' strategy under Greenspan's regime.
Keywords: C51; E52; 330; Central Banker; interest rate smoothing; rational expectations; hybrid Phillips curve; hybrid IS curve; Geldpolitik; Zinspolitik; Kontrolltheorie; Erwartungsbildung; Schätzung; USA